2013
DOI: 10.1002/hyp.9677
|View full text |Cite
|
Sign up to set email alerts
|

Response of hydrology to climate change in the southern Appalachian Mountains using Bayesian inference

Abstract: Predicting long‐term consequences of climate change on hydrologic processes has been limited due to the needs to accommodate the uncertainties in hydrological measurements for calibration, and to account for the uncertainties in the models that would ingest those calibrations and uncertainties in climate predictions as basis for hydrological predictions. We implemented a hierarchical Bayesian (HB) analysis to coherently admit multiple data sources and uncertainties including data inputs, parameters, and model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Increases in temperature and intensity of both wet and dry extremes have been documented in the southern Appalachians and in the southeastern United States Wu, Clark, & Vose, 2014) and are expected to increase with climate change (Carter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in temperature and intensity of both wet and dry extremes have been documented in the southern Appalachians and in the southeastern United States Wu, Clark, & Vose, 2014) and are expected to increase with climate change (Carter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although streams in the southern Appalachians are considered perennial (Sun et al ., ), there are already noticeable changes to the frequency and intensity of rainfall in the region (Laseter, ; Wu et al ., , ). In this study, we demonstrated that water (as discharge) had a major influence on leaf processes in our streams.…”
Section: Discussionmentioning
confidence: 97%
“…Gessner et al, 2010). The predicted change in precipitation and generally lower flows during the summer and autumn months (Wu et al, 2012(Wu et al, , 2014 suggest that ecosystem processes may not be stimulated at a time when leaf inputs are typically maximal and stream invertebrates would have a large availability of food to fuel their production (Whiles & Wallace, 1995;Wallace et al, 1997).…”
Section: Combined Effects and The Future Of Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, future precipitation for the region is expected to increase between 8-10% by 2100, which is similar to the 15% increases predicted for the larger eastern USA (Fernandez and Zegre 2019). Nearby regions of the northeast and southeast US are also expected to experience changes in future P, with P increasing by 3-6% by 2099 , Wu et al 2012.…”
Section: How Has Climate Changed In the Central Appalachian Mountains?mentioning
confidence: 51%